2008
DOI: 10.1007/s00702-008-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of brain 5-HT synthesis but serotonergic neuron formation in Tph2 knockout mice

Abstract: The relative contribution of the two tryptophan hydroxylase (TPH) isoforms, TPH1 and TPH2, to brain serotonergic system function is controversial. To investigate the respective role of TPH2 in neuron serotonin (5-HT) synthesis and the role of 5-HT in brain development, mice with a targeted disruption of Tph2 were generated. The preliminary results indicate that in Tph2 knockout mice raphe neurons are completely devoid of 5-HT, whereas no obvious alteration in morphology and fiber distribution are observed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
138
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(153 citation statements)
references
References 26 publications
11
138
0
3
Order By: Relevance
“…(b) Specification of raphe neurons lacking 5-HT synthesis Several in vitro studies showed a morphogenic effect of 5-HT on proliferation, differentiation, migration and survival of neural cells [80][81][82] 11,14). Conserved particularly is the expression of genes specifying a serotonergic phenotype in raphe neurons lacking 5-HT synthesis.…”
Section: Tph2 In Personality Traits Of Negative Emotionality and In Dmentioning
confidence: 99%
See 2 more Smart Citations
“…(b) Specification of raphe neurons lacking 5-HT synthesis Several in vitro studies showed a morphogenic effect of 5-HT on proliferation, differentiation, migration and survival of neural cells [80][81][82] 11,14). Conserved particularly is the expression of genes specifying a serotonergic phenotype in raphe neurons lacking 5-HT synthesis.…”
Section: Tph2 In Personality Traits Of Negative Emotionality and In Dmentioning
confidence: 99%
“…While perfusion of brain with removal of the residual blood in capillaries resulted in minimal amounts of 5-HT in the rostral raphe region at the lower detection limit (less than 1.2%), it remains possible that a small number of blood components with high 5-HT content, such as platelets or mastocytes, remain trapped in capillaries of brain tissue [14]. Very low brain 5-HT levels were also detected in other Tph2 2/2 mice [21] as well as in Tph1/Tph2 2/2 double KO mice [23].…”
Section: (C) Monoamine Transmitters and Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Illustration of biosynthesis of serotonin (blue arrows), the inhibitor action of telotristat etiprate on TPH (red X), conversion of serotonin to 5-hydroxyindole acetic acid and urinary excretion (green arrows), and activating and inhibitory pathways [20,[24][25][26][27][28].…”
Section: Resistance To Somatostatin Analogsmentioning
confidence: 99%
“…Consequently, it does not diminish central serotonin levels, thus avoiding the side effects that it would entail otherwise [27,28,[52][53][54][55].…”
Section: Telotristat Etipratementioning
confidence: 99%